Study of impedance and radiation properties of a concentric microstrip triangular-ring antenna and its modeling techniques using FDTD method - Misra, I.S.; Chowdhury, S.K. (IEEE transactions on antennas and propagation, 1998)
A concentric microstrip triangular-ring antenna structure using the log-periodic principle for increasing the impedance bandwidth of the microstrip patch antenna is described. The finite-difference time-domain (FDTD) method is applied to analyze the proposed structure. A special technique to model the slanted metallic boundaries of the triangular ring has been used in the general FDTD algorithm to avoid the staircase approximation. The method improves the accuracy of the original FDTD algorithm without increasing the complexity. The radiation patterns at different frequencies over a wide bandwidth are obtained experimentally.